PEMANFAATAN GLISEROL DARI MINYAK JELANTAH SEBAGAI SEDIAAN SPRAY ANTIBAU KAKI YANG MENGANDUNG EKSTRAK ETANOL BIJI KOPI ROBUSTA (Coffea canephora) - Syarifah Nadia; Nurul Karimah; Ernawaty Ernawaty; Supran Hidayat Sihotang; Dea Anggreini; Siti Rahmi Ningrum; Kanne Dachi; Nurmala Sari (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Used cooking oil is a household waste that has the potential to cause environmental pollution if not properly managed. One of its applications is as a raw material for biodiesel production, which generates glycerol as a by-product. This glycerol can be further utilized as a base material for pharmaceutical formulations. Meanwhile, robusta coffee beans (Coffea canephora) are known to contain secondary metabolites with antibacterial properties. This study aimed to utilize glycerol derived from the transesterification of used cooking oil as a base for a foot deodorant spray containing ethanolic extract of robusta coffee beans and to evaluate its physical characteristics and antibacterial activity. This experimental study included the preparation of ethanolic extract of robusta coffee beans using the maceration method, glycerol production from used cooking oil through transesterification, functional group analysis of glycerol using FTIR spectroscopy, and determination of glycerol density. Foot deodorant spray formulations were prepared with varying concentrations of robusta coffee bean ethanolic extract (1%, 2.5%, and 5%). The spray formulations were evaluated for organoleptic properties, pH, viscosity, stability, hedonic test, skin irritation, and antibacterial activity against Staphylococcus aureus using the disc diffusion method. The results showed that glycerol obtained from used cooking oil exhibited characteristic glycerol functional groups and a density of 1.21 g/mL, with a glycerol content of 99.18%. The ethanolic extract of robusta coffee beans contained alkaloids, flavonoids, tannins, steroids/triterpenoids, glycosides, and anthraquinone glycosides. All spray formulations demonstrated acceptable pH values within the physiological skin range, low viscosity, good stability, and no skin irritation. The formulation containing 5% extract showed the highest antibacterial activity against Staphylococcus aureus, with an inhibition zone diameter of 13.7 mm (strong category), and was the most preferred formulation by panelists. In conclusion, glycerol derived from used cooking oil combined with ethanolic extract of robusta coffee beans has strong potential to be developed as a safe, stable, and effective natural-based foot deodorant spray with antibacterial activity.